Science and technology and the president's crime commission past and future - Blumstein, Alfred (Criminology & public policy, 2018)
The U.S. President's Commission on Law Enforcement and Administration of Justice added a Task Force on Science and Technology as somewhat of an afterthought because there had then been very little interaction between science and technology and the criminal justice system (CJS). The task force focused on the CJS as a whole and interactions among its parts, with an important emphasis on analysis of the operating systems and on the important potential role of information systems as the technology advanced. The potential applications of contemporary information and electronic technologies is considerable, especially for assessing risk and needs of identified offenders and for providing relevant information wherever needed. There is urgent need for scientific evaluation of many of the positive and negative aspects of the operation of the CJS and of the potential for new technologies.